2023
DOI: 10.47536/jcrm.v11i1.630
|View full text |Cite
|
Sign up to set email alerts
|

Marine mammal records from Iran

Abstract: Iran has 1,700km of coastline that borders the Persian Gulf and the Arabian Sea in the northwest Indian Ocean. Apart from a handful of records, almost nothing is known about which marine mammal species occur in Iranian waters. This review was conducted to fill this information gap. A total of 127 marine mammal records of 14 species were compiled from Iranian coastal waters. Ninety-nine were from the Persian Gulf, 26 from the Gulf of Oman and 2 were of unknown location. Records of finless porpoise (Neophocaena … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…In Iran, a compilation of marine mammal records from universities, natural history museums, Department of Environment (DoE) offices, Iranian Fisheries Research Organisation (IFRO) centres and various non-governmental wildlife organisations (NGOs) confirmed 25 records of finless porpoise; 23 were from the Persian Gulf and two from the Gulf of Oman (Braulik et al, 2010). Records appear to be concentrated around Bushehr, near the head of the Arabian/Persian Gulf, and Qeshm Island, near the Strait of Hormuz.…”
Section: Arabian/persian Gulf Arabian Sea Bay Of Bengal and Andaman Seamentioning
confidence: 99%
See 1 more Smart Citation
“…In Iran, a compilation of marine mammal records from universities, natural history museums, Department of Environment (DoE) offices, Iranian Fisheries Research Organisation (IFRO) centres and various non-governmental wildlife organisations (NGOs) confirmed 25 records of finless porpoise; 23 were from the Persian Gulf and two from the Gulf of Oman (Braulik et al, 2010). Records appear to be concentrated around Bushehr, near the head of the Arabian/Persian Gulf, and Qeshm Island, near the Strait of Hormuz.…”
Section: Arabian/persian Gulf Arabian Sea Bay Of Bengal and Andaman Seamentioning
confidence: 99%
“…In Taiwan, an analysis of strandings between 2019-20, indicated that of the known causes of death, bycatch accounted the highest proportion or mortality, followed by ship strike and disease (IWC, 2021c). In Kuwait, where cause of death was determined, ship strike accounted for the highest proportion, followed by bycatch of recovered finless porpoise strandings (Nithyanandan and Bohadi, 2021) and in Iran, the high number of bycaught individuals recorded suggests that incidental mortality in fishing gear is unsustainable (Braulik et al, 2010). There is little information on the level of directed take, however, it seems unlikely that this is a significant threat, compared to bycatch.…”
Section: Threatsmentioning
confidence: 99%
“…Conversely, the Iranian coast of the Persian Gulf is thought not to be inhabited by dugongs (Preen, 2004;Braulik et al, 2010). This may be because seagrasses (Order Alismatales), which dugongs exclusively depend on for food (Jefferson et al, 2008), are not distributed uniformly across the sea (Erftemeijer and Shuail, 2012).…”
Section: Journal Of Animal Diversity (2023) | © Lorestan University P...mentioning
confidence: 99%
“…It raises the suspicion that perhaps some of the sightings may have been opportunistic, made by non-scientists, and could have confused the Indo-Pacific finless porpoise, Neophocaena phocaenoides (G. Cuvier), common in HBR, with D. dugon. Neophocaena phocaenoides is widely distributed in the Persian Gulf, including in the shallow Iranian waters (Baldwin et al, 1999;Braulik et al, 2010), and due to their gray color and lack of dorsal fin, are most likely to be confused with D. dugon where their habitats overlap in shallow tropical Indo-Pacific waters (Jefferson et al, 2008).…”
Section: Journal Of Animal Diversity (2023) | © Lorestan University P...mentioning
confidence: 99%
“…have been exposed to multiple environmental stressors. Oil spills from the discharge processes, tanker water depletion, oil well operations, tanker accidents, destruction, and burning of oil rigs and urban runoffs have imposed the Persian Gulf to severe environmental hazards (Nadim et al, 2008;Braulik et al, 2010). Due to the rapid industrial growth in the region and high-density oil facilities as well as the high volume of oil shipments, the risk of oil pollution in this area has signi cantly increased, becoming one of the most anthropogenically impacted regions in the world (Neff., 1979;Mehdinia et al, 2015;Vaughan et al, 2019;Dashtbozorg., 2019).…”
Section: Introductionmentioning
confidence: 99%